The Raven’s Eye. Stylistic references to sight and vision as symbols of knowledge and power (AmS-Skrifter, 2026)
In many cultures throughout history, eye symbolism has a special function in connection with religion, mythology, and superstition. In some mythologies, eyes are linked to birds and their ability to be omnipresent and gather information. In Old Norse written sources, strong, piercing eyes can symbolise power, masculinity, and royal descent, and there is a special eye symbolism associated with the knowledge and esoteric insight that surrounds the one-eyedness of the main god Odin. In this paper, decorative rivets on high-status metal objects from the 5th to 8th centuries AD are interpreted as a stylistic imitation of the characteristic eyes of ravens. The paper takes a closer look at the use of these rivets in relation to eye symbolism in the Scandinavian archaeological material and iconography from the period ca. 200 to 700 AD, drawing further on personal names referring to eyes and ravens and the relations to Old Norse mythology. We suggest that the raven-eye rivets can be seen as representations of Odin’s all-seeing eye and thus his quasi-physical presence, as a way of animating objects, or as symbols of esoteric knowledge. They are therefore interpreted as stylistic traits that were a part of a power symbolism of the elite.